EP.TU.920Modified Surgical Heads-Up Charades – using gamification of surgical topics to enhance learning and make revision enjoyable and useful. (28th October 2021) - Ahmad, Manal; Law, Sarah; Everett, Samuel; Benton, Kirsty; Bamford, Richard; Hunter, Ian
Abstract: Introduction: Gamification has been shown to be successful in surgical education. Charades is an adaptable game and can be utilised as a form of peer learning and adjusted to various levels of knowledge incorporating fun, competition and team working. Method: The project was piloted with a group of Third year medical students. Each player on a team had a short time frame to guess the maximum number of correct answers on the basis of what their colleagues would tell them about the given surgical term to gain points and win. Knowledge based assessments (KBA)were used to determine baseline knowledge and assess learning. A 5 point Likert scale was used to gain feedback from participants. Result: 100% agreed that they found this motivating and engaging, enjoyed this form of revision and would like to participate in this in future and that this helped them to identify gaps in their knowledge. Average scores from KBA's increased from 52.5% to 86% based on new questions from session whilst the score from repeating the initial assessment increased by 10%. Conclusion: Charades is an effective tool for identifying knowledge gaps and developing knowledge base in surgical education and supports the use for gamification as a learning tool.